The Hexactinellid Deep-Water Sponge Vazella pourtalesii (Schmidt, 1870) (Rossellidae) Copes With Temporarily Elevated Concentrations of Suspended Natural Sediment - Wurz, Erik; Beazley, Lindsay; MacDonald, Barry; Kenchington, Ellen; Rapp, Hans Tore; Osinga, Ronald (Frontiers in Marine Science, 2021)
Plumes of re-suspended sediment potentially smother and clog the aquiferous system of filter-feeding sponges with unknown implications for their health. For the first time we examined the physiological responses of repeated exposure to natural sediment in the glass sponge Vazella pourtalesii, which forms dense sponge grounds in Emerald Basin off Nova Scotia, Canada. Ex situ chamber-based measurements of bacterial clearance and oxygen consumption (respiration) rates indicated that individuals subjected to elevated concentrations of suspended sediment expressed normal clearance and respiration rates over 7 days of sediment exposure, indicating an ability to cope with elevated concentrations of indigestible sediment particles. However, clearance rates significantly declined after 14 days of sediment exposure, suggesting an inability to cope with long-term exposure to increased sediment load. Therefore, long-term exposure to elevated concentrations of suspended sediment should be avoided in order to minimize adverse effects on the abundant Vazella sponge grounds.